ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LAMA MENCARI KERJA BAGI TENAGA KERJA TERDIDIK DI KOTA DENPASAR - Aprodita, Bernita Devia; Sudibia, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.11.TAHUN.2023, 2023)
The aim of this research is; (1) to analyze the simultaneous ef ect of education level, marital status, gender, and parents economic status on the length of time looking for work for educated workers in Denpasar City; (2) to analyze the partial ef ect of education level, marital status, gender, and parents' economic status on the length of time looking for work for educated workers in Denpasar City. The data analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that; (1) education level, marital status, gender, and parents economic status simultaneously af ect the length of time looking for work for educated workers in Denpasar City; (2) the higher the level of education, the shorter the period of looking for work compared to educated workers who have a low level of education; (3) the more economically capable parents pay for their children, the longer the period of looking for work is compared to the economic status of parents who are less well of ; (4) educated workers with married status, widowers/widows have a shorter time looking for work than those with unmarried status; (5) educated male workers have a shorter time looking for work than women.